Characterization of a geothermal system in the shallow structure of Seulawah volcano, Indonesia, using transient electromagnetic methods - Marwan, Marwan; Yanis, Muhammad; Abdullah, Faisal; Adhari, Muhammad Ridha; Nugraha, Gartika; Paembonan, Andri Yadi; Idroes, Rinaldi; Yusuf, Muhammad; Dharma, Dian Budi; Muzakir, Muzakir; Saputra, Deni; Ghani, Azman Abdul (International Journal of Renewable Energy Development, 2025)
Seulawah volcano, located in Sumatra, Indonesia, is renowned for its geothermal potential, a crucial source of cleaner energy for Indonesia’s future growth and security. Available studies of Seulawah volcano primarily focus on its general geological, geochemical, and regional characteristics, with limited research on its shallow subsurface conditions. This study aimed to fill this research gap and enhance our understanding of the geothermal system of Seulawah volcano. There are two objectives of this study: (1) to conduct a transient electromagnetic (TEM) survey across the study area and (2) to better visualize and characterize the shallow subsurface conditions of the geothermal system of Seulawah volcano. The TEM method, which employed 60 stations (with distances between stations ranging from 0.5 to 1 km) and intersected several geothermal manifestations as well as local and regional faults, was used to achieve the objectives of this study. The Occam algorithm was applied for 1D inversion of TEM data, which was then validated using magnetotelluric data. The results of this study indicate that the geothermal system of Seulawah volcano has the potential to generate up to 230 Mwe of electrical energy. Moreover, the shallow depth (<200m) of Seulawah volcano is dominated by a resistive zone, which is interpreted to be related to the basaltic rocks of the Lamteuba Formation. The reservoir layer is located at depths of 200–500 m, exhibiting moderate resistivity values of >10 Ωm. At a depth of 500 m, a conductive layer with resistivity values <10 Ωm was observed, interpreted as a clay cap where fluids from the reservoir layer accumulate. Validation with magnetotelluric data shows results consistent with the TEM data, confirming that the findings of this study are reliable. These findings contribute to a deeper understanding of the geothermal system of Seulawah volcano and are expected to support the development of greener, renewable energy sources for Indonesia.